Hydrogen production by water electrolysis: Advances, challenges and future prospects - Zheng ZHANG; Lingjun SONG (工程科学学报)
Achieving global carbon neutrality is one of the key targets set by countries in 2050 to mitigate the adverse effects of climate change. As a clean energy with great potential, hydrogen energy is an important energy solution for this transition because of its high energy density, zero carbon emission, and strong renewability. Electrolytic water hydrogen production has emerged as a key solution for achieving global carbon neutrality goals. This paper investigates the progress and potential of various electrolysis methods, including alkaline water electrolysis, proton exchange membrane (PEM) electrolysis, anion exchange membrane (AEM) electrolysis, and solid oxide electrolyzer cell (SOEC) electrolysis, alongside emerging technologies such as seawater electrolysis and coupled hydrogen production. Alkaline electrolytic water hydrogen production technology occupies an important position in industrial applications owing to its high maturity, low cost and reliability, yet it faces challenges such as current density and gas cross-mixing. PEM technology, known for its high current density, gas purity, and compactness, is hindered by high costs and material corrosion. AEM technology offers cost benefits by avoiding precious metal catalysts and being compatible with low-concentration electrolytes; however, its development is still in the early stages. SOEC technology is promising for its high efficiency at high temperatures but is still in the experimental stage owing to issues such as catalyst deactivation and equipment lifespan. In addition, innovative methods such as seawater electrolysis and coupled hydrogen production offer a sustainable hydrogen production path, although seawater treatment poses technical challenges. Coupled hydrogen production, which links with other small molecule oxidation reactions, improves hydrogen production efficiency but requires further advancements in electrode material selection and reaction rate optimization. Moreover, research is focused on electrolyte additives, such as sulfates, carbonates, and other anionic inhibitors, to improve electrolysis efficiency and reduce corrosion. In catalyst development, new materials and structural improvements are under exploration for improving catalyst activity, stability, and cost-effectiveness. By optimizing system design and component synergy, electrolysis technology for hydrogen production is developing toward improved catalyst performance, reduced energy consumption, and efficient equipment. In particular, integrating electrolytic hydrogen production with renewable energy systems, such as solar and wind, offers an environment-friendly and economical hydrogen production model. In summary, this paper summarizes the current achievements and challenges in electrolysis technology for hydrogen production and provides a valuable reference for future research directions. As science and technology progress, electrolysis technology for hydrogen production will significantly contribute to global carbon neutrality. Governments should implement more supporting policies to promote the commercial application and market growth of this technology, ensuring that it can play a more important role in the future energy transition.